Предмет: Математика, автор: khrebtovatanya

Результат упрощения выражения   frac{a+2 sqrt{ab} +b}{a-b} * frac{a sqrt{a} -b sqrt{b} }{a+b+ sqrt{ab} }
имеет вид:
1) a+b
2) sqrt{a} + sqrt{b}
3) a-b
4)  sqrt{a} - sqrt{b}

Ответы

Автор ответа: NNNLLL54
0
frac{a+2sqrt{ab}+b}{a-b}*frac{asqrt{a}-bsqrt{b}}{a+b+sqrt{ab}}=frac{(sqrt{a}+sqrt{b})^2}{a-b}*frac{(sqrt{a}-sqrt{b})(a+sqrt{ab}+b)}{a+sqrt{ab}+b}=\\=frac{(sqrt{a}+sqrt{b})^2cdot (sqrt{a}-sqrt{b})}{(sqrt{a}-sqrt{b})(sqrt{a}+sqrt{b})}=sqrt{a}+sqrt{b}
Похожие вопросы